Modelling stock returns and risk management in the shipping industry - Sunil Mohanty; Roar Aadland; Sjur Westgaard; Stein Frydenberg; Hilde Lillienskiold; Cecilie Kristensen (Journal of Risk and Financial Management, 2021)
We estimate the impact of macroeconomic risk factors on shipping stock returns, using a quantile regression (QR) model. We regress the excess return of a portfolio for the container, dry bulk, chemical/gas, oil tanker, and diversified shipping sectors on the world market portfolio excess return, volatility index, and changes in the oil price, exchange rate, and interest rate. The sensitivities of stock returns to the risk factors differ across quantiles and shipping segments and are found to be significant for the volatility index, world market portfolio return, exchange rate, and changes in long-term interest rate with variation over quantiles. This provides evidence of asymmetric and heterogeneous dependence between stock returns and certain macroeconomic risk variables. The results of the study also suggest that standard OLS regression is inadequate to uncover the risk-return relation.
Keywords: C32; G10; C22; 330; asymmetric dependence; conditional distribution; ordinary least square; quantile regression; shipping stocks